Modelagem hidrometeorológica associada a um povoamento clonal de eucalipto - Melo Neto, José de Oliveira (2016)
This study aimed to analyze the rainfall partitioning process from a clonal Eucalyptus forest canopy to the soil as well as its effect over the hydro-meteorological conditions of the area. It were carried out both dendrometric and edapho-climatic characterizations of the area relating them to three spacing of plantation (3 x 2; 3 x 3; 3 x 5 m) and to the effects in the water budget of the forest. For water budget conduction, the following variables were studied: throughfall (Pi), stemflow (EsT), overland flow (ESd) and soil-water storage variation in the soil profile (ΔArm), having the evapotranspiration as output (ETr). ETr was split into canopy interception (IL), soil evaporation (Es) and transpiration (Tr). A greater increase in the volume of the trees was observed for 3 x 2 m spacing while the lesser was observed for 3 x 5 m. Observed throughfall accounted for 72.7% of gross precipitation and steamflow, 3.1%. Applying geostatistical procedures, we observed that throughfall has presented spatially structured with strong spatial dependence degree and low estimated errors. It was also observed a gradual increase in the throughfall values as the spacing is increased, being observed a difference of 10.43% between 3 x 2 m spacing compared to 3 x 5 m spacing. In addition, the greater the total rainfall the greater observed stemflow. Greater interception losses were observed for 3 x 2 m spacing (601.5 mm), followed by 3 x 3 m (539.9 mm) and 3 x 5 m (342.9 mm). Observed overland flow throughout the studied period accounted for 163.1 mm. Water storage in the soil profile tends to decrease in the Northeastern/Southwestern direction whereas 3 x 2 spacing presented greater storage (42.7 mm) and 3 x 5 m, the lesser storage (18.8 mm). Observed evapotranspiration in the period was 1631.1 mm (from water budget), which means 102.7% of the gross precipitation, showing that the roots were supplied by water storage in the soil. Soil evaporation corresponded in the observed period to 82.8 mm (5.2 % of the gross precipitation). Estimated transpiration was 1107.3 mm (69.7% of gross precipitation), with 3 x 2 m spacing showing greater efficient in terms of water use (14.4 mm.m-3), followed by 3 x 3 m (28.0 mm.m-3) and 3 x 5 m (31.7 mm.m-3).